Efektivitas Multimedia Interaktif Ayo Lestarikan Lingkungan untuk Meningkatkan Hasil Belajar Kognitif IPAS Siswa Kelas Tinggi SDN 41 Malewang Kabupaten Takalar - Regina Rita Bella; Muhammad Alfian Solo; Nurhikmah H; Suryadi Ishak; Safaruddin (STKIP Subang, 2025)
This study aims to determine the effectiveness of the interactive multimedia Ayo Lestarikan Lingkungan developed using Articulate Storyline 3 in improving students’ cognitive learning outcomes in the IPAS subject. This research employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The participants consisted of 35 fourth, fifth, and sixth-grade students at UPT SDN 41 Malewang, Takalar Regency. The research instrument was a cognitive learning test comprising 15 multiple-choice questions. Data were analyzed using the JASP application through normality testing, homogeneity testing, paired samples t-test, and effect size calculation. The results showed an increase in the average score from 61.00 on the pretest to 77.83 on the posttest. The data met statistical assumptions, with normality p = 0.061 and homogeneity p = 0.060. The paired samples t-test revealed a highly significant difference with t = –8.893 and p < 0.001. The Cohen’s d value of 1.503 indicated a very large effect of the multimedia on students’ cognitive achievement. Thus, the Ayo Lestarikan Lingkungan interactive multimedia based on Articulate Storyline 3 is effective for enhancing students’ cognitive learning outcomes on environmental conservation material.